Effect of Circuit and Interval Training Methods on the Agility and VO₂max of Porprov Football Players in Pati Regency in Terms of Leg Muscle Endurance - Ahmad Badawi; Ahmad Nasrulloh (Physical Education Theory and Methodology, 2023)
This study aimed to determine: (1) the effect of circuit and interval training methods on agility and VO₂max; (2) the difference in the effect of high leg muscle endurance and low leg muscle endurance on agility and VO₂max; (3) the interaction between circuit training, interval training and leg muscle endurance (high and low) on agility and VO₂max.